Conditions of rentability in the apricot industry of Hungary - Apáti, F. (International Journal of Horticultural Science, 2012)
Total investment costs of an up to date apricot plantation requires about 5000 thousand HUF/ha. Modernplantations yield under normal conditions 15–20 t/ha with 80% quality for fresh consumption. Consequently, taking the life span of a plantation (15 years), the internal rate of return of 15–17% per year (IRR), that means that the costs of investment will be regained in the 9–10th year, which is considered to be satisfactory. However, weather hazards (frost, hail) may occur at a probability of 20–25%, therefore, maintaining the quality (80% for fresh consumption) and yields (15–20 t/ha) are badly needed to speak about rentability. This level of yields maintains the option of feasibility up to 20–25% losses.